Differential growth responses to sodium salts involve different ABA catabolism and transport in the halophyte Prosopis strombulifera - Llanes, Analia Susana (2014)
In this work, the response of the halophytic shrub Prosopis strombulifera to lowering an osmotic potential ( o) to -1.0, -1.9, and -2.6 MPa generated by NaCl, Na2SO4, and the iso-osmotic combination of them was studied at 6, 12, and 24 h after reaching such values in the growing media. By analyzing the content of abscisic acid (ABA) and related metabolites and transpiration rates, we observed that ABA content varied depending on type of salt, salt concentration, organ analyzed, and age of a plant. ABA content in leaves was much higher than in roots, presumably because of rapid biosynthesis and transport from roots. Leaves of Na2SO4-treated plants had the highest ABA content at o -2.6 MPa (24 h) associated with sulfate toxicity symptoms. Significant content of ABA-glucose ester (ABA-GE) was found in both the roots and leaves, whereas only low content of phaseic acid (PA) and dihydrophaseic acid (DPA). The roots showed high ABA-GE accumulation in all treatments. The highest content of free ABA was correlated with ABA-GE glucosidase activity. The results show that ABA-GE and free ABA work together to create a specific stress signal.